The cost‐effectiveness of universal hepatitis B screening for reaching WHO diagnosis targets in Australia by 2030. Issue 4 (3rd January 2023) - Xiao, Yinzong; Hellard, Margaret E; Thompson, Alexander J; Seaman, Christopher; Howell, Jess; Scott, Nick
Abstract: Objectives: To assess the impact on diagnosis targets, cost, and cost‐effectiveness of universal hepatitis B screening in Australia. Design: Markov model simulation of disease and care cascade progression for people with chronic hepatitis B in Australia. Setting: Three scenarios were compared: 1. no change to current hepatitis B virus (HBV) testing practice; 2. universal screening strategy, with the aim of achieving the WHO diagnosis target by 2030 (90% of people with chronic hepatitis B diagnosed), based on opportunistic (general practitioner‐initiated) screening for HBsAg; 3. universal screening strategy, and also ensuring that 50% of people with chronic hepatitis B are receiving appropriate clinical management by 2030. Main outcome measures: Projected care cascade for people with chronic hepatitis B, cumulative number of HBV‐related deaths, intervention costs, and health utility (quality‐adjusted life‐years [QALYs] gained during 2020–2030). An incremental cost‐effectiveness ratio (ICER) threshold ( v scenario 1) of $50 000 per QALY gained was applied. Results: Compared with scenario 1, 80 HBV‐related deaths (interquartile range [IQR], 41–127 deaths) were averted during 2020–2030 in scenario 2, 315 HBV‐related deaths (IQR, 211–454 deaths) in scenario 3. Scenario 2 cost $84 million (IQR, $41–106 million) more than scenario 1 during 2020–2030 (+8%), yielding an ICER of $104 921 (IQR, $49 587–107 952) per QALY gained. Scenario 3 cost $263 million (IQR, $214–316 million) more than scenario 1 during 2020–2030 (+24%), yielding an ICER of $47 341 (IQR, $32 643–58 200) per QALY gained. Scenario 3 remained cost‐effective if the test positivity rate was higher than 0.35% or the additional costs per person tested did not exceed $4.02. Conclusions: Universal screening for hepatitis B will be cost‐effective only if the cost of testing is kept low and people receive appropriate clinical management.